The 'OCTAPAC' culture as a core component of HRD climate: a survey - Shaari, Roziana (2015)
The concept of Human Resource Development (HRD) requires a specific and congenial climate to flourish. In other words, it can be said that success of HRD in an organization depends on the existence of a favorable HRD climate. HRD climate deals with the interactions among employees within the organization from different levels using a set of techniques to achieve the objectives of the organization and to ensure the development of the employees who share similar culture that enhances productivity and spirit of innovation. This paper measures HRD culture known as “OCTAPAC culture” as first introduced by Rao and Abraham 1986. In order to understand how it can be function as a source of sustained competitive advantage, this study investigated the practices of OCTAPAC in the Ministry of Education headquarters in the Sultanate of Oman. According to Rao and Abraham model, OCTAPAC culture is determined to be a core component of HRD climate.